2017
DOI: 10.1177/2333794x17711767
|View full text |Cite
|
Sign up to set email alerts
|

Why Are We Cutting? A Survey of Cultural Views on Circumcision in the Texas Panhandle

Abstract: To determine the factors that may contribute to parents’ decision to circumcise their son in the Texas Panhandle region, voluntary surveys were distributed to all mothers with term male newborns during the mandatory discharge planning class. The father being circumcised (P < .0001), Caucasian (P < .05), and some graduate school of the caregiver (P < .011) were factors most correlated with newborns being circumcised. Newborns of Hispanic origin, those having Medicaid insurance, and a Catholic affiliation were l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
(15 reference statements)
1
4
0
Order By: Relevance
“…While a relationship between advanced parental education and higher MC rates has been reported within the literature, it remains unclear what specifically may be contributing to this preference, and what impact parental education may have with regards to MC appearance. 12 As aforementioned, our study demonstrated a preference for shorter collars in respondents with a graduate degree. Similarly, certain faiths (i.e., Judaism and Islam) have institutionalized the practice of circumcision, yet do not distinctly identify a preferred appearance for MC.…”
Section: Callegari Et Al Preferences In Mucosal Collar Length Post-ci...supporting
confidence: 71%
See 1 more Smart Citation
“…While a relationship between advanced parental education and higher MC rates has been reported within the literature, it remains unclear what specifically may be contributing to this preference, and what impact parental education may have with regards to MC appearance. 12 As aforementioned, our study demonstrated a preference for shorter collars in respondents with a graduate degree. Similarly, certain faiths (i.e., Judaism and Islam) have institutionalized the practice of circumcision, yet do not distinctly identify a preferred appearance for MC.…”
Section: Callegari Et Al Preferences In Mucosal Collar Length Post-ci...supporting
confidence: 71%
“…The strongest known reported influence on MC rates has been the circumcision status of the father. 12,13 Rediger et al demonstrated this within a prospective review of expecting parents, noting that amongst children born to circumcised fathers, 82% were likely to undergo circumcision as compared to only 15% of children born to uncircumcised fathers. 13 Analysis from our survey corroborates this finding in that 78% of circumcised fathers had their son circumcised compared to only 18% of sons of uncircumcised males (P<0.05).…”
Section: Callegari Et Al Preferences In Mucosal Collar Length Post-ci...mentioning
confidence: 98%
“…It was in accordance with several studies which established that the circumcision status of the father was the most significant factor associated with the decision. [ 12 13 ] It seemed that some of them still thought that circumcision is an unsafe procedure. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…Many other studies have investigated the factors that influence a guardian's decision for circumcision, and have shown health, hygiene, and cosmetic appearance among the most important [7][8][9][10][11][12]. A study by Williamson and Williamson showed that Midwestern mothers surveyed on their decision to circumcise their sons identified hygiene and appearance as the two major decision-making factors [13].…”
Section: Discussionmentioning
confidence: 99%